analisis model keterkaitan gayakepemimpinan, iklim organisasi, karakterristikindividu, kepuasan kerja,komitmen organisasi dan kinerja karyawanpada perusahaan daerah air minum (pdam)tirta mangutama kabupaten badung - I Made Purba Astakoni (Forum Manajemen STIMI Handayani Denpasar, 2014)
The success of the empowerment of human resources in an organizationis realized by the performance of its employees. Employees are an importantresource for the organization, because it has a talent, energy and creativity thatneeded by the organization. Such as Perusahaan Daerah Air Minum (PDAM)TirtaMangutamaBadung regency. The objectives of the study is : (1) to determine theeffect of leadership style to job satisfaction, (2) to determine the effect of organizationclimate to job satisfaction, (3) to determine the effect of individual characteristics toan organization commitment, (4) to determine the effect of organization climate to anorganization commitment, (5) to determine the effect of employee job satisfaction toan organization commitment (6) to determine the effect of organization commitment tothe employee performance. To determine the answer of the above research goals, thequestionnaire have distributed to 160 employees as a respondents. The data collectedwere analyzed byStructural Equation Model (SEM). The usage of SEM methods wasevaluated prior to the normality of the data, confirmatory factor analysis (CFA) andthen influence analyzes of the SEM. The initial full models showed that the model isnot good, and the modifications needed to obtain the Goodness of Fit. The resultsof these research indicate, that the sixth hypothesis show a positive effect.Basedon the square multiple correlation coefficient, the employee performance variables,only 36.00% influenced by leadership style, job satisfaction, organization climate,individual characteristics and organization commitment.There are other variablesto be observed and implemented, in order to improve employee performance.